California: 'the Stem Cell State''. (November 2011) - Thomas, Jonathan
Interview with Jonathan Thomas We talked to Jonathan Thomas, newly elected Chairman of the California Institute for Regenerative Medicine (CIRM), a few weeks into a role he describes as "the opportunity of the lifetime" to find out what he sees as the key goals for the CIRM and why patient advocates are so critical to the future of the Institute. Jonathan Thomas was elected as Chairman of the California Institute for Regenerative Medicine (CIRM) in June 2011, succeeding the Founder and former Chairman, Bob Klein. Thomas has had a successful career in finance and law and is a Co-Founding Partner at Saybrook Capital, an investment banking and private equity firm. His commitment to patient advocacy and keen interest in biological sciences, developed as a Biology Major at Yale, led him to stand for Chairman.